2018
DOI: 10.1302/1863-2548.12.180034
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and treatment preferences for developmental dysplasia of the hip: A survey of EPOS and POSNA members

Abstract: PurposeThe aim of this study was to elucidate developmental dysplasia of the hip (DDH) diagnosis and treatment preferences among members of the Pediatric Orthopaedic Society of North America (POSNA) and European Paediatric Orthopaedic Society (EPOS).MethodsA 54-question survey on DDH diagnosis and treatment preferences was distributed to POSNA and EPOS members. Descriptive statistics were performed.ResultsA total of 459 responses were analyzed. Ultrasound was the preferred modality for diagnosing DDH in infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 11 publications
1
63
0
Order By: Relevance
“… 5 A recent survey showed that 76% of POSNA members never used traction, indicating decreased use of traction during the last decades. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 5 A recent survey showed that 76% of POSNA members never used traction, indicating decreased use of traction during the last decades. 6 …”
Section: Introductionmentioning
confidence: 99%
“…The Pavlik harness is the most popular dynamic splint. Other dynamic splints used for treating DDH are the Tubingen splint, Frejka pillow, Von Rosen splint, Aberdeen splint, Coxaflex and Teufel brace [6][7][8][9][10][11][12]. The static splints promote a "rigid reduction".…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial research, high-quality comparative studies continue to be lacking and the treatment of DDH is mainly based on the clinical experience of the treating surgeon [ 3 ]. This variability in opinion became evident in a 2018 survey of EPOS and POSNA members on their preferred treatment methods for DDH [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative measures are more effective before the age of 6 months and include a variety of techniques such as the Pavlik harness splint [ 5 ], the Tubigen hip flexion splint [ 6 ], closed reduction plus spica casting and Sommerville- Petit method of traction [ 7 ]. According to the 2018 DDH survey, in spite of marked disparity between surgeons, closed reduction is usually not favored prior to 3 months or open reduction before 6 months of age [ 4 ]. Surgical Stabilization might be required in cases with failed conservative treatment, residual dysplasia or older children with neglected DDH.…”
Section: Introductionmentioning
confidence: 99%